Pengaruh Kebijakan Dividen, Kebijakan Utang, dan Pertumbuhan Perusahaan terhadap Harga Saham - Nurochman, Ali; Hunein, Hamida (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to provide empirical evidence of the effect of Dividend Policy, Debt Policy, and Company Growth on Stock Prices. This study uses a quantitative approach and the data used is secondary data. The population in this study were Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. The method in determining the sample uses purposive sampling. Obtained a sample of 25 companies with a period of 5 years. The data analysis technique used is multiple linear regression analysis. The F test results show that simultaneously Dividend Policy, Debt Policy, and Company Growth have a significant effect on Stock Prices. The t test results show that the Dividend Policy partially has a positive effect on stock prices, but the Debt Policy partially has no significant effect and Company Growth partially has no significant effect.